Estudio económico financiero para la implementación de una microempresa procesadora de pasta de cacao en el cantón Pasaje - Salvador Tomaselli, Katherine Lucía (2012)
This project describes the process of implementing a micro processor of cocoa paste, to be lo-cated in Canton Passage, to take advantage of the availability of raw materials and provide value-added product to be marketed as allowing a good quality paste flavored and aroma. In this paper we define the optimal parameters with which it must process the grain, in order to maintain the organoleptic characteristics from the drying up of tempered and packaged prod-uct. The basic minimum conditions required by the Rules of Good Manufacturing Practice for Processed Foods. Cocoa paste as a finished product is designed to meet the demand for raw material processing industries require chocolates, chocolate paste for companies engaged in the confectionery and pharmaceutical and cosmetic companies as Ecuacocoa, Incacao, Ede Ecua-cocoa, Incacao, Edeca, Colcacao of Guayaquil.Was necessary to determine the amount of investment in fixed assets, the minimum capital of opera-tion, the projected net cash flow to ten years to undertake micro-sadora process cocoa paste.Economic and financial analysis conducted for the company to scale up its activities are determined to require a total investment of 50 $ 033.04, consisting of land and buildings, ma-chinery and equipment and other assets eventually comprising goods and supplies for the ad-ministrative area and sales. The minimum capital required for year zero is 611 $ 517.39. For the company to have cash to buy raw materials, direct materials and payment of direct labor in the first 50 months must have $ 964.28 in this case the purchase of cocoa as a raw material is generated higher cost due to the value of each bushel. The 10-year projected flow is positive, which indicates that the company will have sufficient liquidity to meet creditors, make new investments in the purchase of machinery and technology to improve product quality and achieve high levels of competitiveness . According to financial analysis, return on sales will be obtained is 6.1% and net profit on capital per dollar of assets will be 0.28 cents in the first year.